Topical Imiquimod for the Treatment of Relapsed Cutaneous Langerhans Cell Histiocytosis after Chemotherapy in an Elderly Patient - Shinsaku Imashuku; Miyako Kobayashi; Yoichi Nishii; Keisuke Nishimura (Case Reports in Dermatological Medicine)
Diagnosis and treatment of Langerhans cell histiocytosis (LCH) in elderly patients are often difficult. We report here a 61-year-old female suffering from a refractory axillary ulcer for nearly a year, whose biopsy revealed LCH. It was also noted that the patient had other cutaneous papulovesicular eruptions of LCH as well as central diabetes insipidus. The patient was first successfully treated with multiagent chemotherapy (cytosine arabinoside/vinblastine/prednisolone). DDAVP also well controlled diabetes insipidus; however, the axillary ulcer and cutaneous LCH relapsed. Thereafter, we found topical imiquimod to be effective in the treatment of relapsed cutaneous LCH lesions.